PERBANDINGAN PERFORMA DAN KEAMANAN VOICE OVER INTERNET PROTOKOL DENGAN DAN TANPA OPEN VIRTUAL PRIVATE NETWORK (STUDI KASUS KOS GAYAM) - Yulkarnain, Dani; Raharjo, Suwanto; Lestari, Uning (Jurnal Jarkom, 2013)
ABSTRACT VoIP (Voice Over Internet Protocol) is a system that used by sending data package from one place to another places such as voice or video use mediator IP Address in a internet network. VoIP transmission voice signal by change to the digital form and it can be categorized be data packages that sent by using platform IP. However, the weakness of VoIP is security is not guaranteed. Because IP based, so anybody can tap and record the data of VoIP. So, it needs a security system to overcome that security problem. One of the solutions is by implement of OpenVPN (Virtual Private Network). OpenVPN is one method to overcome the security network in sending the data package. To implement that idea so, it made a system VoIP OpenVPN. Then analyze   how to Performa the sending of voice or video that resulted and the security of VoIP before and after used OpenVPN. Before using OpenVPN, data package VoIP that sent can be record and replay the data payload it also can be caught and can be saw. The Performa of sending data in the busy network it also can be long delayed. However, after using OpenVPN, the package data VoIP cannot record and replay and data payload also cannot catch. The Performa VoIP OpenVPN in busy network is better than VoIP without OpenVPN. Keywords : VoIP, OpenVPN, Performa, Security